COMPARATIVE EVALUATION OF COMPREHENSIVE AND CONVENTIONAL THERAPEUTIC STRATEGIES IN PATIENTS WITH CHRONIC VIRAL HEPATITIS B (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents the findings of a study evaluating the dental status of patients with chronic viral hepatitis B (CHB). The frequency of key oral symptoms and pathologies was assessed depending on the type of therapy received, and the results were compared with those of a control group. The data obtained confirm that the oral cavity reflects the overall somatic condition of the body and becomes involved in the pathological process associated with chronic viral hepatitis.